Evaluasi Usabilitas Situs Web Pemerintah Kabupaten Mojokerto Dengan Menggunakan Discrepancy Evaluation Model (DEM) - Noor Dwi Indah Lestari; Admaja Dwi Herlambang; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In this research, the process of usability evaluation is using model from Discrepancy Evaluation Model (DEM) to find out the extent of the gap that occurred on the website of Kabupaten Mojokerto. The gap that was intented is the difference from the current state of the website (performance) to standards in guidelines for website development. This research also using usability evaluation tool which is Website Usability Evaluation (WEBUSE) as an evaluator of the evaluation results that give direction to recommendation for the improvement of what to do. The result from this research it is known that Content, Organization, and Readability having usability value equal to 0,677 and in good category, the value of Navigation and Links variable is 0,585 with moderate category, User Interface Design variable has value 0,484 with moderate category, and Performance and Effectiveness variable having usability value equal to 0,523 with moderate category. In assessment using WEBUSE explained that when the variable has entered into excellent level, then that variable has been able to be trusted by users of the system, so it can be seen that there is still gap on usability of Kabupaten Mojokerto website.